2022
DOI: 10.1177/09564624221126867
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of HIV pre-exposure prophylaxis among men who have sex with men using apps for sexual encounters in Turkiye

Abstract: Background New HIV diagnoses are rising in Turkiye. Men who have sex with men (MSM) are estimated to be the main driver of the epidemic. Pre-exposure prophylaxis (PrEP) was proven to be effective in reducing new HIV diagnoses and PrEP recently became available in Turkiye. Objective To assess awareness of and willingness to use PrEP and the level of off-licence use among MSM. Methods An anonymous self-completed questionnaire was sent out over the Hornet Gay Social Network from December 2019 to February 2020, av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…30,32,33 Although there is no study from Turkiye specifically examining the perception of HIV risk and testing frequencies among various populations, a recent Hornet survey on HIV pre-exposure prophylaxis showed that a high percentage (63%) of MSM had never tested for HIV. 34 The major barriers to testing at the patient level were identified as low-risk perception and fear of HIV disease and disclosure concerns. 35,36 Fear of being stigmatized for HIV and for sexual orientation may also have contributed to nontesting.…”
Section: Discussionmentioning
confidence: 99%
“…30,32,33 Although there is no study from Turkiye specifically examining the perception of HIV risk and testing frequencies among various populations, a recent Hornet survey on HIV pre-exposure prophylaxis showed that a high percentage (63%) of MSM had never tested for HIV. 34 The major barriers to testing at the patient level were identified as low-risk perception and fear of HIV disease and disclosure concerns. 35,36 Fear of being stigmatized for HIV and for sexual orientation may also have contributed to nontesting.…”
Section: Discussionmentioning
confidence: 99%
“…A large-scale survey including the general population in Britain suggested that the majority of those who reported practicing unsafe sex did not have a high perceived risk of HIV infection [ 36 ]. There are also disparities in PrEP awareness and risk perception among other vulnerable groups such as ethnic minorities, women, and displaced people [ 36 , 37 , 38 ]. People with lower education levels and low risk perception are reported to have significantly lower interest in using PrEP [ 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Türkiye was among the countries with no PrEP availability. A Hornet survey including more than 4700 respondents from Türkiye reported that approximately 40% of respondents were aware of PrEP, 2.5% had used PrEP in the previous year, and 1.7% were current users, primarily through the internet and pharmacies, which was off label use ( 29 ). Respondents younger than 25 years who are considered most at risk, were significantly less aware of and less willing to use PrEP compared to older respondents.…”
Section: Clinical and Research Consequencesmentioning
confidence: 99%